Features of the Regional Political Process: The Case of Russia - Vladimirivich, Sokolov Alexander (Mediterranean Journal of Social Sciences, 2012)
In the period of 1999-2007 Russia’s development was characterized by rapid economic recovery, increased welfare ofcitizens, and formation of robust and stable political system. Actually the political competition was minimized at the federal level. Thiswas achieved both by means of forming new institutional framework for the political process and political competition, and through directstruggle of political actors. Visible political competition, political opposition, and political protest disappeared in many of regions of theRussian Federation. The Financial Crisis, which started in 2008, radically changed the economic situation in Russia. As a resultnumerous protests were organized in many towns and regions. Regional opposition political groups used actively the current criticalsituation for the political struggle. It is becoming more difficult for the officials, political parties loyal to the government, and actors of theregional political process to maneuver between the critical socio-economic situation and the necessity of displaying loyalty to federalruling elite.